The Relative Importance of Sexual Reproduction versus Clonal Spread in an Aridland Bunchgrass - Liston, A.; B. L. Wilson; Robinson, W. A.; P. S. Doescher; N. R. Harris; Svejcar, T. (Oecologia, 2003)
Festuca idahoensis (Idaho fescue) is a perennial caespitose grass, common in semi-arid rangelands of the Intermountain West. To determine how individuals are recruited into a population, we studied two long-term monitoring plots that were established in 1937 at the Northern Great Basin Experimental Range in southeastern Oregon. The plots measured 3.05×3.05 m, and were located approximately 30 m apart. One plot was ungrazed, the other was subject to moderate levels of cattle grazing. The number of F. idahoensis plants in both plots increased ten-fold between 1937 and 1996, but whether this was due primarily to reproduction by seed or clonal fragmentation was unknown. In 1996, we mapped and sampled 160 plants of F. idahoensis. We used dominant inter-simple sequence repeat (ISSR) markers and codominant allozyme markers in order to identify genetic individuals and measure genetic diversity. Both plots were characterized by high levels of genetic and clonal diversity. When information from ISSRs, allozymes and sample location were combined, 126 genets were recognized, each consisting of one to four samples (ramets). By measuring the diameter of clones surrounding plants that were present in 1937, we estimated that clonal spread occurred at a rate of approximately 3.7 cm per decade, and thus was of secondary importance in the maintenance and increase of F. idahoensis stands. Sexual reproduction, rather than clonal fragmentation, accounted for most of the recruitment of new plants into these plots. The grazed plot had fewer ramets, genotypes, and clones than the ungrazed plot, but the ramets were significantly larger. Levels of genetic diversity did not differ in the grazed and ungrazed plots, but there was some evidence for a small, but significant level of genetic differentiation between the two. The results also indicate that F. idahoensis has the potential to be a long-lived species with some individuals persisting in excess of 60 years. This study demonstrates how long-term monitoring can be supplemented by genetic analysis to obtain detailed information on the population dynamics of plants. In the case of this community dominant species, this provides essential information for understanding succession and developing management and restoration strategies.